Measuring the Role of Right and Left Hemispheres in Processing Arabic by the Methods of Visual field and Dual-Task Performance - Al-Hamouri, Firas (Jordan Journal of Educational Sciences, 2006)
The present study investigated the efficiency of the visual field and the dual- task performance methods in studying Arabic language processing among 40 Arabic native speakers at Yarmouk University. Results of both experiments confirmed those of previous studies that showed the importance of left hemisphere in processing language. In the first experiment, subjects showed more advantage of the right visual field (left hemisphere) than the left visual field (right hemisphere). In the second experiment, subjects also showed more interference between the tapping task and the linguistic task using their right hand (left hemisphere) than using their left hand (right hemisphere). No significant effects were found for sex in the visual field method, nor in the dual-task performance one